2016
DOI: 10.1098/rsta.2015.0286
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric transport of trace elements and nutrients to the oceans

Abstract: This paper reviews atmospheric inputs of trace elements and nutrients to the oceans in the context of the GEOTRACES programme and provides new data from two Atlantic GEOTRACES cruises. We consider the deposition of nitrogen to the oceans, which is now dominated by anthropogenic emissions, the deposition of mineral dust and related trace elements, and the deposition of other trace elements which have a mixture of anthropogenic and dust sources. We then consider the solubility (as a surrogate for bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 79 publications
5
74
1
Order By: Relevance
“…Although in the literature there are recent estimates of trace metals solubility from dust (e.g., Chance et al, ; López‐García et al, ; Mackey et al, ; Ravelo‐Pérez et al, ; Winton et al, ), solubility percentages are usually as variable as reported values of atmospheric dust deposition in the ocean. The reasons for such variability include the origin, load, and geochemical characteristics of dust (Baker et al, ; Jickells et al, ; Sholkovitz et al, ) as well as a lack of consensus among the methodologies used for its estimation (Meskhidze et al, ; Raiswell et al, ; Schulz et al, ). Thus, to calculate the atmospheric supply of soluble metals from the total fluxes of Fe and Mn, we selected as the most representative for our study, Fe and Mn solubility percentages reported for soils from the nearest semiarid region and dust samples from the coastal portion of the CCS.…”
Section: Methodsmentioning
confidence: 99%
“…Although in the literature there are recent estimates of trace metals solubility from dust (e.g., Chance et al, ; López‐García et al, ; Mackey et al, ; Ravelo‐Pérez et al, ; Winton et al, ), solubility percentages are usually as variable as reported values of atmospheric dust deposition in the ocean. The reasons for such variability include the origin, load, and geochemical characteristics of dust (Baker et al, ; Jickells et al, ; Sholkovitz et al, ) as well as a lack of consensus among the methodologies used for its estimation (Meskhidze et al, ; Raiswell et al, ; Schulz et al, ). Thus, to calculate the atmospheric supply of soluble metals from the total fluxes of Fe and Mn, we selected as the most representative for our study, Fe and Mn solubility percentages reported for soils from the nearest semiarid region and dust samples from the coastal portion of the CCS.…”
Section: Methodsmentioning
confidence: 99%
“…The Cd and Pb contents of the leachates were subsequently determined by inductively coupled plasma–mass spectrometry (ICP‐MS) (Text S2). Results for the size‐fractionated sample SF7 were reported previously [ Jickells et al , ].…”
Section: Samples and Analytical Techniquesmentioning
confidence: 99%
“…Fe solubility estimates range from 0.001 to 90 % (Aguilar-Islas et al, 2010;Baker et al, 2016). The fractional solubility (herein referred to as "solubility") of aerosol TEs is defined in terms of the amount of a TE in solution from any given leach that passes through a filter (usually < 0.45 or 0.2 µm), expressed as a percentage of the total (Baker and Croot, 2010;Baker et al, 2016;Jickells et al, 2016). While this operational definition accounts for some of the variability in published values, it does not account for all of it.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the GEOTRACES programme has produced a number of aerosol datasets, which has stimulated further discussion on the use of these data to look for trends that link TE solubility and aerosol source (e.g. Baker et al, 2016;Jickells et al, 2016). Elemental ratios, enrichment factors, and air mass back trajectory (AMBT) simulations have long been used as a first approximation of aerosol source, and there are many studies that employ multivariate statistical analyses for aerosol source apportionment (e.g.…”
Section: Introductionmentioning
confidence: 99%